Peran Orang Tua Dalam Pendidikan Anak di Era Covid- 19 - Rukiat Rukiat; Nurminawati Nurmionawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
This study aims to find out how the role of parents in children's education in the Covid-19 era, explain the various barriers to online learning, and explain the various efforts of parents to overcome obstacles to online learning at home, given the importance of children's education in the Covid-19 era. produced a generation of ulil albab in the village of Sukajadi rt 03. In this study, the researcher tried to find out what roles parents had to play, the obstacles and also the efforts that needed to be made in the online learning process in the village of Sukajadi rt 03. Hope this research provides inspiration for other parents, or for researchers and readers in general, as an additional reference that is used by the wider community.